PENGARUH DISIPLIN KERJA, BUDAYA KERJA DAN KOMPETENSI TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT MATAKALI KABUPATEN POLEWALI MANDAR - Rahmatiah Rahmatiah; Maryadi Maryadi; Didiek Handayani Gusti (Jurnal Aplikasi Manajemen & Kewirausahaan MASSARO, 2022)
This study aims to analyze the influence of work culture on job satisfaction, the effect ofwork discipline on job satisfaction, the influence of work culture on the performance of ASN, Theeffect of work discipline on the performance of ASN. the effect of job satisfaction on theperformance of ASN. the effect of job satisfaction as an intervening variable on the influence ofwork culture. the effect of job satisfaction as an intervening variable on the effect of workdiscipline on ASN performance.The population in this study were all offices of the Regional Secretariat of PolewaliMandar Regency, amounting to 131 people with the consideration that the data and informationneeded were easier to obtain and accurate and very relevant to the subject matter that became theobject of this research. Sampling of this study was carried out using the solvin technique with asignificant standard of 10%. the sample used in this study was ASN at the Regional Secretariat ofPolewali Mandar Regency, totaling 57 ASN. The data collection technique was carried outthrough a questionnaire/questionnaire where each respondent's answer was assessed using ascore according to a Likert scale.